FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA SATUAN KERJA POLITEKNIK NEGERI BANDUNG - Lili Indrawati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Accrual Government Accounting Standards (SAP) is a government accounting standard that records and acknowledges transaction, at the time the contract of transaction occur, regardless of the receipts or payment of cash and cash equivalents.  The issuence of Government Regulation (PP) no 71 year 2010 concerning SAP revising PP 24 year 2005 concerning SAP, hence both central government and also regional are obliged to apply accrual based accounting during accounting and preparation of financial report.  Based on this, the purpose of this study is to determine what factors affect the succes of the accrual-based SAP application in the units of Bandung State Polytechnic.  This research is conducted by qualitative method with emphasis on interpretive approach.  Data analysis is carried out through three steps, namely: 1) Data collection, 2) Data redustion, 3) Data presentation, and 4) Decesion making or verification.  The result showed that: 1) The environment/condition oriented to the application of accrual accounting is very supportive; 2) existing regulation can be applied without constraints; 3) human resources are competent; 4) software help completion of work; 5) the existing hardware already supports and in accordance with the software; 6) financial statement can be completed and sent on time.Keywords: Success Factor, Accrual Bases, Bandung State Polytechnic